Perfectionism as Causes of Academic Procrastination at Collage?: A Sytematic Review (International Journal of Scientific Research and Management (IJSRM), 2024)
Procrastination is a common problem faced by many students, generally defined as the act of procrastinating on tasks or decisions without rational reasons. This systematic review investigates the factors and impacts of procrastination, especially in academics. A literature search was carried out on publications written in English on selected investigation topics using a database, namely Scopus. Only research investigated academic procrastination and there were 15 articles international which reveals the factors and impacts of procrastination from 107 articles that have been found in the database. The results of our systematic review found that students have a variety of factors and impacts of the procrastination phenomenon as well as various factors and impacts of procrastination that students experience from an internal and external perspective. There is abuse of addictive substances and other activities that trigger increased procrastination in students.